Measuring Justice and Child Protection: A Juridical Study of the Marriage Dispensation After the Enactment of Law Number 16 of 2019 - Vivi Novita Yulambangsari; Ucuk Agiyanto; Nurul Iman (LPPM Institut Pendidikan Nusantara Global, 2026)
The revision of Law Number 1 of 1974 through Law Number 16 of 2019 brought significant legal changes, particularly regarding the setting of the minimum age for marriage at 19 years for both men and women. This policy was designed to improve child protection and reduce the number of early marriages. However, the continued prevalence of marriage dispensation requests in religious courts indicates that the implementation of this regulation has not been fully effective and still leaves problems at the level of legal application. This study aims to examine the legal regulations regarding marriage dispensation after the enactment of Law Number 16 of 2019, identify the basis for judges' considerations in deciding dispensation cases, and evaluate the extent to which these decisions reflect the principles of justice and child protection. The approach used is normative juridical, combining analysis of legislation and case studies. Primary, secondary, and tertiary legal materials are analyzed qualitatively to gain a comprehensive understanding. The research findings reveal that although the minimum age for marriage has been raised, the existence of marriage dispensation still creates room for suboptimal child protection goals. Judges' considerations generally relate to empirical circumstances such as out-of-wedlock pregnancy and the family's socio-economic issues. However, not all of these considerations align with the principle of the child's best interests. Therefore, strengthened regulations and oversight mechanisms are needed for the practice of granting dispensations to maximize the principles of justice and child protection.